Educational interventions for malnutrition in Mexican children - Beltrán Rodríguez, María Guadalupe (Mexican Journal of Medical Research ICSA, 2021)
INTRODUCTION: Malnutrition is the leading cause of infant morbidity and mortality worldwide. In 2019, 21% of children living in rural areas have chronic malnutrition and 24% of children under 12 years of age in the country are overweight or obese. MATERIAL AND METHOD: The objective of this article was to know the characteristics of the educational treaties for malnutrition. The search for articles and documents made in PUBMED, EBSCO, GOOGLE SCHOOLAR and government and international pages. RESULTS: 28 nutritional educational interventions were analysed. 21.4% of the studies carried out were in the state of Sonora, almost 57% of the studies were of a quasi-experimental type. The most used strategies in complications include Exhibition of theoretical and practical content; use of games (table, crossword puzzles, memoramas, etc.); physical activity and use of audiovisual media. 96% of the studies carried out had statistically affected differences with p values ​​from .05 to .000. CONCLUSIONS: The educational practices must be carried out in a holistic way determined by the following aspects: Elements of knowledge and food practices; Psycho-emotional elements; Sociocultural elements and economic elements.